Histories of HIV/AIDS in Western Europe New and regional perspectives - Weston, Janet; Elizabeth, Hannah J. (Manchester University Press, 2022)
The early 2020s marked the fortieth anniversary of the first confirmed cases of AIDS and a new wave of historical interest in the ongoing epidemic. This edited collection showcases some of this exciting new work, with a particular focus on less well-known histories from western Europe. Featuring research from social, cultural and public historians, sociologists and area studies scholars, its eight chapters address experiences, events and memories across regions and nations including Scotland, Wales, Italy, Norway and the Netherlands, paying careful attention to often-overlooked groups including drug users, sex workers, nurses, mothers and people in prison. Offering new perspectives on the development and implementation of policy, the nature of activism and expertise and which (or whose) histories are remembered, it is essential reading not only for historians of health but also for all those working in HIV/AIDS studies.